Proceedings of the 2013 ACM International Joint Conference on Pervasive and Ubiquitous Computing 2013
DOI: 10.1145/2493432.2493452
|View full text |Cite
|
Sign up to set email alerts
|

Contextual dissonance

Abstract: The Experience Sampling Method (ESM) has been widely used to collect longitudinal survey data from participants; in this domain, smartphone sensors are now used to augment the context-awareness of sampling strategies. In this paper, we study the effect of ESM design choices on the inferences that can be made from participants sensor data, and on the variance in survey responses that can be collected. In particular, we answer the question: are the behavioural inferences that a researcher makes with a trigger-de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(13 citation statements)
references
References 22 publications
0
13
0
Order By: Relevance
“…This option was only available before the notification was pushed into notification bar. Additionally, the survey notifications were only allowed to pop up between 8:00 AM and 10:00 PM [45]. To reduce the workload of the participants, the time interval between two surveys was at least one and half hours.…”
Section: Methodsmentioning
confidence: 99%
“…This option was only available before the notification was pushed into notification bar. Additionally, the survey notifications were only allowed to pop up between 8:00 AM and 10:00 PM [45]. To reduce the workload of the participants, the time interval between two surveys was at least one and half hours.…”
Section: Methodsmentioning
confidence: 99%
“…The importance of survey timing depending on participant characteristics was highlighted in additional work by Lathia et. al [21]. They showed that a response bias caused by simplistic trigger design gives rise to contextual dissonance.…”
Section: ) Lack Of Participant Customisationmentioning
confidence: 99%
“…The large majority of studies asking for participant input (e.g., via ESM) is following a randomised or interval-based time schedule [2]. Although these may initially appear to provide the most equal distribution of participant responses, response rates are often not equally distributed throughout the day -resulting in certain contexts being overrepresented in the collected data [20,21]. Building on the aforementioned ambition towards integrated active and passive sensing, contextual information can inform researchers when participants are likely to be available and able to provide reliable input [22,21].…”
Section: Research Agenda On Human Accuracy In Mobile Data Collectionmentioning
confidence: 99%